Aus der Arbeit der Bibliothek des Deutschen Entomologischen Instituts: Nachlaß Julius Lederer, Wien. - Marwinski, Felicitas (Contributions to Entomology = Beiträge zur Entomologie, 1970)
A list of correspondents was compiled from the papers left by lepidopterologist Julius Lederer (1821-1870) which are now in Deutsches Entomologisches Institut.